Picture and Picture Models Helpful Application Milkshakes for Increasing Interest in Learning Writing Skills Text Explanation - Annisa Herayani; Teti Sobari; Enung Nurhayati (JLER (Journal of Language Education Research), 2024)
This research article is motivated by the problem of students' lack of interest in learning in explanatory text writing skills which is caused by the use of learning media and learning models that seem ordinary and do not attract students' attention, resulting in a decrease in students' interest in learning. This article aims to determine students' responses to the Picture and Picture model assisted by the Milkshake application and to determine students' ability to write explanation texts. The method used in this research is a qualitative descriptive method with data collection techniques through questionnaires and tests. Research result show that the Picture and Picture model help Milkshake app has good response​ For used in learning , with an average of 73% response student . Next , results test knowledge and skills average 84 percent after implementation was carried out, thus it was stated that the ability of all class.